Tunable coupling ratio for optical switch application - Saktioto; Hanim, Nor Faridah; Fadhali, M.; Yupapin, Preecha; Ali, Jalil (My University, 2010)
This paper describes the breakdown voltage of SiO2 fiber using Pockel's effect and empirical equation. The model is evaluated by coupling coefficient and refractive index changes. A 1×2 single-mode directional coupler switch has been fabricated. A large electro-optic effect causes a change in the optical properties when a slowly varying electric field is applied. A model to describe the breakdown voltage for driving the optical switch of the fusion SiO2 fiber coupler has been developed. A voltage is applied through sectioned electrodes along the coupling length. This model uses the coupling coefficient and the changes in the refractive index to describe the optical switching. The change of refractive index due to the linear electro-optic Pockel effect and an empirical equation are used to calculate the value of coupling coefficient. The result shows that the changes of the refractive index increases exponentially as a function of separation fiber axis from 5 to 8 μm. The breakdown voltage and refractive indices difference depict a linear relationship. The increment of coupling coefficient shows that the value of voltage is reduced. © 2010 SPIE.
Keywords: Coupling coefficient; Coupling ratio; Optical switch; Pockel effect